Educational software for stress analysis of idealized closed thin walled sections - Syed Mohamed Ali, Jaffar; Nur Fadhila, Hasna; Makame, Burhani; Riyadh, Miah Mohammed (2018)
Aerospace structures are typical semi-monocoque structures that are made up of thin-walled closed section reinforced with stiffeners. Stress analysis of such closed thin-walled structures which are statically indeterminate is tedious and time consuming. An educational software which can aid students in stress analysis of such idealized thin-walled closed sections has been developed. The software enables students to select different types of wing torsion box sections with stiffeners, which may be subjected to bending, shear or torsional loads and evaluate the resulting stresses on it. The software allows the student to idealize a selected twin spar unsymmetrical wing section with multiple booms under multiple loads. Results from this software have been validated against the results in the literature. The software has been developed using MATLAB with graphical user interface (GUI) which is very user friendly. The software is expected to be a very useful tool for effec-tive teaching learning of courses on thin-walled structures and automotive/aircraft structures.